Raising Rockstar: How Parental Involvement Fosters Resilience in Children - Ria Novianti; Ainama Nafisa Putri; Tengku Nila Fadhlia (AL-ISHLAH: Jurnal Pendidikan, 2025)
Resilience in early childhood is a critical developmental capacity that enables children to adapt positively to challenges. Parental involvement is widely recognized as a key protective factor in fostering resilience, yet research on this relationship in early childhood, particularly within the Indonesian context, remains limited. This study employed a quantitative, cross-sectional design to examine the relationship between parental involvement and resilience in early childhood. Data were collected from 163 mothers of children aged 0–6 years in Sumatra, Indonesia, using two validated instruments: the RMS-25 to assess children's resilience and the Hoover-Dempsey Sandler Parental Involvement Questionnaire. Data were analyzed using SmartPLS 3.0 to assess the path relationship between variables. The results revealed a significant positive effect of parental involvement on children’s resilience (β = 0.606, R² = 0.367, p 0.05). The model showed good fit indices, indicating robust structural validity. Key aspects of parental involvement, such as emotional support, communication, and engagement in daily learning, were found to be positively associated with higher levels of resilience. These findings align with developmental theories that highlight the vital role of the family environment in shaping children’s psychosocial outcomes. The study underscores the importance of emotionally responsive and involved parenting in promoting adaptive functioning in early childhood. This study contributes to the limited body of research on early childhood resilience in Indonesia and suggests practical implications for the development of parenting programs aimed at strengthening children’s emotional and adaptive capacities.